2018
DOI: 10.1080/16070658.2018.1551767
|View full text |Cite
|
Sign up to set email alerts
|

Availability of adequately iodised salt at household level and its associated factors in Robe town, Bale Zone, South East Ethiopia: community-based cross-sectional study

Abstract: Background: Iodine is a micronutrient required by the body in small amounts to prevent iodine deficiency disorder (IDD), which is a global public health concern. There were no specific data at household level of adequately iodised salt in the study area. Thus this study aimed to assess availability of adequately iodised salt and its associated factors at household level in Bale-Robe, South East Ethiopia. Methods: A community-based cross-sectional study was conducted in Robe town, Bale Zone, South East Ethiopia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 5 publications
4
5
1
Order By: Relevance
“…Similarly, those households who were from high community education level had higher chance of iodized salt use compared with households from low community education level. This finding is similar with the finding of other studies in Ethiopia [ 24 , 26 28 ]. This could be due to participants who had education are more likely to be knowledgeable on the use of iodized salt than those who did not have education [ 26 , 36 38 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similarly, those households who were from high community education level had higher chance of iodized salt use compared with households from low community education level. This finding is similar with the finding of other studies in Ethiopia [ 24 , 26 28 ]. This could be due to participants who had education are more likely to be knowledgeable on the use of iodized salt than those who did not have education [ 26 , 36 38 ].…”
Section: Discussionsupporting
confidence: 93%
“…Several factors are known to affect iodized salt utilization. Most importantly, being female, married [19,20], having knowledge on IDD and iodized salt [19,[21][22][23][24][25], higher educational status [24,[26][27][28], and higher monthly income [26,27,29] are significantly associated with iodized salt utilization.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of regression analysis to know about the associated factors of knowledge, it was found that educational status and attitude score were significantly associated with knowledge score (p < 0.01). However, age was not statistically significant (p > 0.05), which was similar to a study conducted in southeast Ethiopia where researchers said that the knowledge of respondents reduced with low educational status determined by binary logistic regression [22]. In our study, the percentage of positive attitude was lower (16.2%) than the percentage of respondents being indifferent (41%) and having negative (42.8%) attitudes.…”
Section: Discussionsupporting
confidence: 79%
“…The majority (67.5%) of them stored salt for less than two-months; almost similar to Karmakar et al, where 76% of women stored salt for less than one month [19]. Nevertheless, dissimilar to Dida et al as in his study, almost all people (93%) preserved salt for less than sixty days [22].…”
Section: Discussionsupporting
confidence: 74%
“…Other cross-sectional studies in different parts of Ethiopia have found such variables to be determinants for iodized salt availability in the household. 24,26,27 There have been regional differences in household iodized salt coverage in this study as well as previous studies. 28 From literature including recent analysis from EDHS, these geographical differences might arise from lack of access to messages regarding the use of iodized salt which may encompassed the lack of access to mass media, 29,30 another factor could be market availability of iodized salt.…”
Section: Discussionsupporting
confidence: 76%